Levonorgestrel-releasing intrauterine system vs. usual medical treatment for menorrhagia: an economic evaluation alongside a randomised controlled trial - Sanghera, Sabina; Roberts, Tracy Elizabeth; Barton, Pelham; Frew, Emma; Daniels, Jane; Middleton, Lee; Gennard, Laura; Kai, Joe; Gupta, Janesh Kumar (Public Library of Science, 2014)
Objective: To undertake an economic evaluation alongside the largest randomised controlled trial comparing Levonorgestrel-releasing intrauterine device (‘LNG-IUS’) and usual medical treatment for women with menorrhagia in primary care; and compare the cost-effectiveness findings using two alternative measures of quality of life.